El Régimen Presidencial en la Constitución de 1993 - Bernales Ballesteros, Enrique (Pontificia Universidad Católica del Perú, 2016)
In this article, the author makes a critical analysis of the political regime in the 1993 Constitution. He begins analyzing the institution of the Presidency of the Republic, along with its vices and defects, criticizing the concentration of power in the figure of the President and the authoritarian management of his attributions, characteristics that are meaningless in a republic system. Thus, he concludes with a new vision of the figure of the President of the Republic and his attributions in order to achieve an improvement in the functioning and efficiency of the State, without affecting the democratic balance.

En el presente artículo, el autor realiza un análisis crítico del régimen político en la Constitución de 1993. Comienza analizando la institución de la presidencia de la República, junto con sus vicios y defectos, criticando así la concentración de poder en la figura del Presidente y el manejo autoritario de sus atribuciones, características que carecen de sentido en un Sistema Republicano. Así concluye con una nueva visión de la figura del Presidente de la República y sus atribuciones para lograr una mejora en el funcionamiento y eficiencia del Estado, sin afectar el equilibrio democrático.
The Presidential Regime in the 1993 Constitution
Keywords: Democracy; Presidential Regime; Constitution; State; Power; Government; Democracia; Régimen Presidencial; Constitución; Estado; Poder; Gobierno; https://purl.org/pe-repo/ocde/ford#5.05.00